Copper to Fibre Migration: Regulated Access Fees Incentivising Migration - Fabian Eltges; Niklas Fourberg; Lukas Wiewiorra (International Telecommunications Society (ITS), 2022)
Consumer sided demand migration from legacy to fibre telecommunication technologies is a key challenge in today's economic policy. We adapt Chen and Riordan (2007) Spokes Model of spatial competition to capture a duopolistic multi-product firm setting in which an incumbent operator and an entrant firm simultaneously offer both a fibre and a copper based product. Consumer preferences are uniformly distributed over the preference space consisting of four spokes (2 products of 2 suppliers). The novelty of our approach is that we allow for a per-unit access fee which is paid by the entrant to the incumbent as prerequisite for offering its own copper based end-user product. Using the access fee as a strategic variable for either the incumbent or a regulating social planner, we compare different scenarios to investigate its role as a potential instrument to induce copper to fibre migration. We find that the access fee acts as an asymmetric cost pass-through for the entrant to promote its fibre product at the expense of its copper access. Furthermore, the socially optimal fee will be either identical to the private solution or smaller, if consumer preferences are strong. If one considers demand for fibre products as the desired objective, our results suggest that the privately chosen access fee already implies full copper to fibre migration. However, if a social planner is responsible for setting access fees, the fee can be utilised to increase demand for fibre products beyond the socially (welfare) desirable level.
Keywords: 330